'To minimise that risk, there are some costs we incur': Examining the impact of gender-based violence on the urban poor. Issue 5 (3rd May 2020) - Maclin, Beth J.; Bustamante, Nirma D.; Wild, Hannah; Patel, Ronak B.
ABSTRACT: Urban environments marked by violence create fear that can have real impacts on the urban poor, particularly women and girls. Any efforts to tackle poverty and promote health must address the impacts to their access to livelihoods and education, healthcare, markets, and social support that underlie wellbeing. This study aimed to elucidate specific impacts that violence and fear have on the very poor in rapidly growing cities and the coping strategies employed. This multi-country qualitative study was conducted in Dhaka, Bangladesh, Port-au-Prince, Haiti; and Addis Ababa, Ethiopia. Participants in all three cities employed similar tactics to avoid violence. People adjusted how, when, and where they travel and how they interact with people who threaten them. These coping strategies led participants to spend more money on goods and to restrict access to livelihood opportunities, education, healthcare, and social activities. Women are impacted more than men in all spheres and city specific differences are highlighted. Residents of urban slums, particularly women, in these three cities cope with urban violence in many ways, suffering consequences in a range of categories – leading to significant impacts to their own health and well-being and their families.